The European renaissance : centres and peripheries - Burke, Peter (Oxford, Uk; Cambridge, Ma. : Blackwell, 1998)
This is a fascinating account of the geography, chronology and sociology of one of the major cultural movements in European history. It provides an original examination of the Renaissance across the whole of the continent.
Peter Burke begins by examining the conditions in which innovation took place in cultural centers such as Florence, Avignon, Flanders and Rome in the fourteenth and fifteenth centuries. But his emphasis falls on the late Renaissance, c.1530-1630, when the new cultural forms and ideas reached the Celtic, Scandinavian and Slav peripheries. He discusses the process of the active reception or creative imitation of classical and Italian models at the level of everyday life as well as that of art, literature and music, noting the importance of the reproduction of famous works of art by means of engravings and ceramics. He also examines the social and political structures which shaped local responses to the movement. The book concludes with an assessment of the effects of the Renaissance movement on later centuries, including its contribution to the "Europeanization" of Europe.
Str. [256]-274: Bibliografija
Kazalo
Keywords: kulturna povijest; renesansa